Tablighi Jama’ah and Politics - Bukhori Bukhori; Dzar Al Giftar (UIN Sunan Gunung Djati, 2023)
This research addresses the prevalent community rumors regarding the Tablighi Jama'ah's aversion to political discourse. The veracity of this claim is confirmed through an examination of the Jama'ah's foundational teachings, notably the